Influence of Sub-Inhibitory Dosage of Cefotaxime on Multidrug Resistant Staphylococcus haemolyticus Isolated from Sick Neonatal Care Unit - Madhurima Chakraborty; Taniya Bardhan; Manjari Basu; Bornali Bhattacharjee (MDPI AG, 2022)
Staphylococcus haemolyticus has emerged to be a frequently encountered late-onset sepsis pathogen among newborn infants. Critical care of neonates involves substantial usage of antibiotics and these pathogens are often exposed to sub-optimal doses of antibiotics which can augment maintenance of selection determinants and a range of physiological effects, prime among them being biofilm formation. Therefore, in this study, the outcome of a sub-inhibitory dosage of a commonly prescribed third-generation antibiotic, cefotaxime (CTX), on multidrug resistant (MDR) S. haemolyticus, was investigated. A total of 19 CTX-resistant, MDR and 5 CTX-susceptible strains isolated from neonates were included. Biofilm-forming abilities of S. haemolyticus isolates in the presence of sub-optimal CTX (30 μg/mL) were determined by crystal violet assays and extracellular DNA (eDNA) quantitation. CTX was found to significantly enhance biofilm production among the non-susceptible isolates (p-valueWilcoxintest-0.000008) with an increase in eDNA levels (p-valueWilcoxintest-0.000004). Further, in the absence of antibiotic selection in vitro, populations of MDR isolates, JNM56C1 and JNM60C2 remained antibiotic non-susceptible after >500 generations of growth. These findings demonstrate that sub-optimal concentration of CTX induces biofilm formation and short-term non-exposure to antibiotics does not alter non-susceptibility among S. haemolyticus isolates under the tested conditions.